Study on solar sources and polar cap absorption events recorded in Antarctica - L. PERRONE; A. MELONI; M. DAMASSO; M. GALLIANI; PARISI, Mario (Advances in Space Research, 2009)
Particularly intense events occurred on the Sun in a period around minimum of solar activity during cycle 23. We investigated the characteristics of September 2005 and December 2006 events and the properties of the correlated observations of ionospheric absorption, obtained by a 30 MHz riometer installed at Mario Zucchelli Station (MZS-Antarctica), and of geomagnetic activity recorded at Scott Base (Antarctica). Solar events are studied using the characteristics of CMEs measured with SoHO/LASCO coronagraphs and the temporal evolution of solar energetic protons in different energy ranges measured by GOES 11 spacecraft. Analysing these data, we have determined how these effects are finally observed on the Earth’s surface not only in the ionospheric absorption of radio waves and in the intense geomagnetic activity, but also as significant variations of cosmic ray modulation, even at high energies. © 2009 COSPAR. Published by Elsevier Ltd. All rights reserved.